Investigating the perceived emotional experience of bilinguals in the acquisition of first and second languages: KIRKHS students as a case study - Ahmad H.Osman, Rahmah; Jaffer, Usman (International Association of Computer Science and Information Technology Press (IACSIT), 2012)
When indulging in any piece of literature, one generally experiences the emotions contained in that piece. While this rings true for a reader reading a piece in their first language, users of a second language claim to be less emotional in their second language generally and especially whilst reading literature. This study therefore embarks on investigating the perceived emotional experience of bilinguals when reading poetry in their native language (Malay) and their second language (Arabic). It also investigates whether learning in the form of literary skills and text familiarity plays a key role in experiencing emotion in second language poetry. 60 participants were exposed to 5 poems in their native language and second language respectively. A self-report emotion scale (PANAS) was administered before and after each language exposure. They were then taught the poems. After a week they were once again exposed to the same second language poems and 5 new second language poems. The (PANAS) scale was once again administered before and after. The results show that text familiarity has a significant effect on emotional experience in second language users.